A NEPHROPROTECTIVE EFFECT OF CARISSA SPINARUM AGAINST GENTAMICIN INDUCED OXIDATIVE NEPHROTOXICITY - Bharadwaj, Soumya; Sanwal, Ritu (International Journal of Research -GRANTHAALAYAH, 2024)
One of the most prevalent issues with the kidneys is nephrotoxicity, which happens when the body is exposed to a toxin or medicine. With the growing availability of powerful therapeutic medications such as aminoglycoside antibiotics, chemotherapeutic agents, and nonsteroidal anti-inflammatory drugs (NSAIDs), a variety of pharmaceuticals can have a negative impact on the kidney, leading to acute renal failure, chronic interstitial nephritis, and nephritic syndrome. Ethiopian native Carissa spinarum (Apocynaceae) is traditionally used to treat skin conditions, rheumatism, diarrhoea, chicken pox, and stomachaches. The herbal plant Carissa spinarum possesses antioxidant qualities. The term "nephrotoxicity" describes the detrimental effects that different drugs can have on the kidneys, which can result in damage and dysfunction. This illness offers a serious risk to kidney health and can be brought on by exposure to specific medicines, chemicals, or poisons. Understanding the methods by which these substances affect the structure and function of the kidneys—such as oxidative stress, inflammation, and interference with essential cellular processes—is necessary to comprehend the abstract idea of nephrotoxicity. Nephrotoxicity management also involves establishing prevention and management strategies, identifying, and tracking possible nephrotoxic substances, and managing and preventing nephrotoxicity. All things considered, an abstract comprehension of nephrotoxicity entails investigating the complex pathways and circumstances that lead to renal injury and formulating strategies to lessen or offset these detrimental effects on kidney function.